The Home for Wayward Girls : a novel - Bradley, Marcia (HarperCollins Publishers, 2023)
Growing up in the 1990s, Loretta knows little of life beyond the Home for Wayward Girls, the secluded ranch where her parents run a program designed to "correct" teen girls' "bad behavior." Loretta witnesses firsthand how the adults use abusive discipline to crush these young women's spirits and break their wills. Since childhood she's been afraid of her father, and avoids him by spending time with the residents, secretly teaching them the survival skills they'll need in case they manage to escape. One day, a horrifying act of violence forces Loretta to flee the ranch herself. Eventually finding safety and a sympathetic community, Loretta dedicates herself to working with lost, vulnerable, and defenseless teens, determined to prevent the same thing from happening to other girls like her.